2020
DOI: 10.21203/rs.2.20312/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of cataract and its associated factors among adults aged 40 years and above in Waghimra zone, Amhara, Northeast Ethiopia: A Community based cross-sectional study

Abstract: Background Cataract is a major cause of avoidable blindness worldwide. Its greatest burden found in low-income countries. Therefore, knowing the prevalence and identification of risk-factors would be crucial in planning strategies to delay its development.Objective To assess prevalence and associated factors of cataract among adults aged 40 years and above in Waghimra Zone, Amhara, Ethiopia, 2019.Methods A cross-sectional study was undertaken among 528 adults in Waghimra Zone. Multi stage sampling technique wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Participants with single marital status were 2.9 times (AOR = 9.583, 95% CI: (2.840, 32.342)) more likely to develop cataract than married individuals. Similar study was reported in Ethiopia, 26 Ghana, 15 Kenya, the Philippines and Bangladesh, in which individuals with single marital status were more likely to develop cataract than married individuals. This is because being married is a protective mechanism from developing cataract.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Participants with single marital status were 2.9 times (AOR = 9.583, 95% CI: (2.840, 32.342)) more likely to develop cataract than married individuals. Similar study was reported in Ethiopia, 26 Ghana, 15 Kenya, the Philippines and Bangladesh, in which individuals with single marital status were more likely to develop cataract than married individuals. This is because being married is a protective mechanism from developing cataract.…”
Section: Discussionsupporting
confidence: 85%
“…Participants in the age group of 70-79 years were 9.6 times more likely to develop cataract than those in the age group of 40-49 years (AOR = 9.583, 95% CI: (2.840, 32.342)). This was supported by studies conducted in Ethiopia, Waghimra Zone, 26 Nigeria 16 and India, 29 in which the probability of developing cataract for older individuals is more likely than younger individuals. All these studies taken individually and as a group demonstrate that cataract increases with age.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation